2015
DOI: 10.1007/s00113-015-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Augmentationstechnik am proximalen Femur

Abstract: In addition to the optimal surgical treatment, secondary prevention such as osteoporosis management to avoid further fractures is crucial in the treatment of these patients. This article is based on the current literature and provides an overview of the possible applications of cement augmentation for the treatment of proximal femoral fractures. In addition the surgical approach as well as previous scientific data on an established osteosynthesis using cement-augmented PFNA for the treatment of pertrochanteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…Therefore, despite the higher costs and not reaching statistical significance, this might confirm the higher stability of augmented femoral neck blades in patients with severe osteoporosis. In line with the literature [ 12 , 13 , 14 , 15 ], there was no significant difference in the cut-out rate between the groups. Due to the low overall cut-out rate of less than 1%, the study cohort needs to be even larger than the 620 evaluated patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, despite the higher costs and not reaching statistical significance, this might confirm the higher stability of augmented femoral neck blades in patients with severe osteoporosis. In line with the literature [ 12 , 13 , 14 , 15 ], there was no significant difference in the cut-out rate between the groups. Due to the low overall cut-out rate of less than 1%, the study cohort needs to be even larger than the 620 evaluated patients.…”
Section: Discussionsupporting
confidence: 89%
“…One of the most commonly used implants today for treating proximal femoral fractures is the PFNA (“proximal femur nail anti-rotation”; DePuy Synthes). To increase stability in the femoral head, the perforated helical femoral neck blade can be augmented with cement [ 12 ]. Biomechanical experiments have shown higher osteosynthesis stability by cement augmentation of the femoral neck blade.…”
Section: Introductionmentioning
confidence: 99%
“…Hierzu erfolgt nach der Implantation zunächst die Applikation eines Kontrastmittels über die Klinge zum Ausschluss einer intraartikulären Leckage. Anschließend werden 3-6 ml PMMA-Zement appliziert [31]. Biomechanische Studien zeigen eine signifikant höhere Primärstabilität nach Zementaugmentation mit gesteigerter axialer Belastbarkeit bis zum Versagen der Osteosynthese [32,33].…”
Section: Zementaugmentationunclassified
“…To this end, a contrast agent is first applied over the blade after implantation to rule out intra-articular leakage. Subsequently, 3-6 ml PMMA cement is applied [31]. Biomechanical studies have shown significantly higher primary stability following cement augmentation with increased axial load-bearing capacity until osteosynthesis failure [32,33].…”
Section: Cement Augmentationmentioning
confidence: 99%
“…As a result, proximal femur fractures are associated with a high one-year mortality rate of up to 30% [2]. The treatment goal of proximal femur fractures must therefore ensure the preservation of function and independence in orthogeriatric patients [3]. Among proximal femur fractures, the per/subtrochanteric fracture is most common, followed by femoral neck fractures [4].…”
Section: Introductionmentioning
confidence: 99%